A study of the translation of architecture terms in the architects' data Neufert" between English and Vietnamese = Nghiên cứu cách dịch các thuật ngữ kiến trúc trong cuốn dữ liệu kiến trúc sư Neufer giữa tiếng Anh và tiếng Việt. M.A Thesis Linguistics: 60 - Vũ, Hải Yến (ĐHNN, 2017)
M.A. Thesis English Linguistics -- College of Foreign Languages. Vietnam National University, Hanoi, 2009